Uncovering Financial Statement Fraud in Indonesian Banks: A Post-COVID Fraud Hexagon Perspective - Kusumaningsih, Damayanti; Sulistyowati, Sri (Master of Accounting Universitas Trunojoyo Madura, 2026)
Financial statement fraud remains a critical issue in the banking sector, particularly in the post-COVID-19 period marked by economic uncertainty and performance pressure. This study aims to examine the factors influencing financial statement fraud in banking companies listed on the Indonesia Stock Exchange during 2023–2024 based on the fraud hexagon approach. This research employs a quantitative method using multiple linear regression analysis on 86 samples selected through purposive sampling. The findings indicate that financial stability and external pressure have a negative effect on financial statement fraud, while director change and ineffective monitoring have a positive effect. Meanwhile, auditor change, CEO’s picture frequency, political connections, and government projects do not significantly affect financial statement fraud. This study recommends strengthening corporate governance mechanisms and encouraging investors to exercise greater caution in assessing fraud risk within the banking sector.